Efficacy and safety of clopidogrel only vs. clopidogrel added proton pump inhibitors in the treatment of patients with coronary heart disease after percutaneous coronary intervention: A systematic review and meta-analysis. (June 2019) - Pang, Jun; Wu, Qiang; Zhang, Zheng; Zheng, Tong-zhang; Xiang, Qiuling; Zhang, Ping; Liu, Xiaoqiao; Zhang, Changhai; Tan, Hongwen; Huang, Jing; Liu, Wei; Song, Fang; et al.
Abstract: Background: Controversy still exists that whether clopidogrel should add proton pump inhibitors (PPIs) in patients with coronary heart disease after percutaneous coronary intervention (PCI). The aim of this study was to evaluate the efficacy and safety of clopidogrel added proton pump inhibitors (PPIs) vs. clopidogrel for the treatment of patients with coronary heart disease after percutaneous coronary intervention (PCI). Methods and results: We systematically searched PubMed, EMBASE, Web of Science, the Chinese Biomedical Medical Literature database, and the Cochrane Library for all clinical trials that were published on this topic through October 2018. We specifically selected the clinical trials that evaluated the efficacy and safety of clopidogrel added proton pump inhibitors vs. clopidogrel in the treatment of patients with coronary heart disease after PCI. RevMan 5.0 software was used for quantitative data analyses. 15 randomized controlled trials including 50, 366 patients were included. The meta-analysis results showed that compared with the clopidogrel added PPI group, the non-PPI group had significantly less risk of MACE[RR = 0.82, 95%CI:0.77–0.88], myocardial infarction recurrence[RR = 0.72, 95%CI:0.57–0.90], stent thrombosis[RR = 0.71, 95%CI:0.56–0.92], Target vessel revascularization (TVR)[RR = 0.77, 95%CI:0.63–0.93] and stroke [RR = 0.72, 95%CI:0.67–0.76]. The risks of all cause death [RR = 1.14, 95%CI:0.85–1.51], cardiovascular death [RR = 1.14, 95% CI: 0.85–1.52], bleedings events [RR = 1.60, 95%CI:0.53–4.81] were similar in the two groups. Conclusions: The patients in the non-PPI group were observed to be associated with less risk of MACE, myocardial infarction recurrence, stent thrombosis, target vessel revascularization (TVR) and stroke. And the two groups had similar all cause death, cardiovascular death, bleedings events.